Traces of Religious Pluralism in the Indonesian Ulama Exegesis Manuscripts - Imron Rosidi; Munzir Hitami; Imam Hanafi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
This article is based on a literature study with a focus on several verses of the Qur’an that are related to religious pluralism. The objects of study are interpretations written by several Muslim scholars and Nusantara intellectuals. Amid the importance of awareness of religious pluralism in Indonesia, studying the commentators who live in different places and times, with different backgrounds and writing commentaries in different languages, but still in the Indonesian context is very important to do. From these differences and similarities, the following article seeks to find common ground and different points of which more or less give a picture of the heterogeneous interpretation of the Muslim scholars in the archipelago (Indonesia). But in interpreting the verses of religious pluralism, they are at one conclusion that; First, acknowledging the existence of other religions; Second , giving the right to coexist with each other in respect of other religions without any element of suspicion . Third , prohibiting elements of coercion in religion, and Fourth, recognition of safety in each religion